Associations between serum concentrations of perfluoroalkyl substances and DNA methylation in women exposed through drinking water: A pilot study in Ronneby, Sweden. (December 2020) - Xu, Yiyi; Jurkovic-Mlakar, Simona; Lindh, Christian H.; Scott, Kristin; Fletcher, Tony; Jakobsson, Kristina; Engström, Karin
Highlights: DNA methylation in women upon exposure to perfluoroalkyl substances (PFAS) 117 differentially methylated positions (DMPs) were associated with PFAS exposure. A near-significantly differentially methylated region in S100A13 was identified. PFAS exposure was not associated with epigenetic age acceleration. In silico analyses suggest several canonical pathways associated to genes with DMPs. Abstract: Background: Perfluoroalkyl substances (PFAS) are widespread synthetic substances with various adverse health effects. A potential mechanism of toxicity for PFAS is via epigenetic changes, such as DNA methylation. However, few studies have evaluated associations between PFAS exposure and DNA methylation among adults, and data is especially scarce for women. Furthermore, exposure to environmental pollutants has been associated with epigenetic age acceleration, but no studies have yet evaluated whether PFAS is associated with epigenetic age acceleration. Objectives: To investigate whether exposure to PFAS is associated with alteration of DNA methylation and epigenetic age acceleration among women. Methods: In this observational pilot study, 59 women (aged 20–47 years at enrollment in 2014) from Ronneby, Sweden, an area with historically high PFAS exposure due to local drinking water contamination, were divided into three PFAS exposure groups (low, medium, and high). Genome-wide methylation of whole-blood DNA was analyzed using the Infinium MethylationEPIC BeadChip. Ingenuity Pathway Analysis was used for in silico functional assessment. Epigenetic age acceleration was derived from the DNA methylation data using Horvath's epigenetic skin and blood clock. Results: 117 differentially methylated positions ( q < 0.017) and one near-significantly differentially methylated region ( S100A13, FWER = 0.020) were identified. In silico functional analyses suggested that genes with altered DNA methylation ( q < 0.05) were annotated to cancer, endocrine system disorders, reproductive system disease, as well as pathways such as estrogen receptor signaling, cardiac hypertrophy signaling, PPARα/RXRα activation and telomerase signaling. No differences in epigenetic age acceleration between PFAS exposure groups were noted ( p = 0.43). Conclusion: The data suggests that PFAS exposure alters DNA methylation in women highly exposed to PFAS from drinking water. The observed associations should be verified in larger cohorts, and it should also be further investigated whether these changes in methylation also underlie potential phenotypic changes and/or adverse health effects of PFAS.